Infección por SARS-COV-2 en trabajadores de la salud: análisis de riesgo epidemiológico en una institución de alta complejidad de Bogotá, Colombia, 2020 - Milcíades Ibáñez-Pinilla (Infectio, 2022)
Objective: To determine the incidence of SARS-CoV-2 infection and its association with sociodemographic, clinical, and occupational characteristics in health workers (HCWs) in the COVID-19 risk area.Material and method: Longitudinal analytical study in a cohort of TS from the “Zafiro” area of patients with suspected or confirmed diagnosis of SARS-CoV-2 infection. The identification of positive cases of SARS-CoV-2 was carried out with the RT-PCR test.Results: The cohort was made up of 114 SWs, with an average age of 35.3±7.4 years, with positions as general practitioner (26.3%), nursing assistant (21.1%) and nurse (19.3%). The incidence rate of SARS-CoV-2 (31.6%) and reinfection (1.8%) during seven months. The factors jointly associated with SARS-CoV-2: cohabitation with people at high risk of contagion (HR=2.406, 95% CI: 1.225, 4.726, p=0.011), the lowest educational level (HR=2.241, 95% C: 1.051, 4.782, p=0.037) and a higher consumption of sleep medications (HR=4.680, 95% CI: 1.328,16.486, p=0.016).Conclusions: The contagion rate of SARS-CoV-2 during seven months of the pandemic, in health workers was high (one in three SW) associated with cohabitation with high-risk people, lower educational level and higher consumption of medications for to sleep. A situation of concern in the HCWs was the suspected cases of SARS-CoV-2 reinfection.